Massively parallel quantum chemical density matrix renormalization group method. Issue 8 (30th December 2020) - Brabec, Jiri; Brandejs, Jan; Kowalski, Karol; Xantheas, Sotiris; Legeza, Örs; Veis, Libor
Abstract: We present, to the best of our knowledge, the first attempt to exploit the super‐computer platform for quantum chemical density matrix renormalization group (QC‐DMRG) calculations. We have developed the parallel scheme based on the in‐house MPI global memory library, which combines operator and symmetry sector parallelisms, and tested its performance on three different molecules, all typical candidates for QC‐DMRG calculations. In case of the largest calculation, which is the nitrogenase FeMo cofactor cluster with the active space comprising 113 electrons in 76 orbitals and bond dimension equal to 6000, our parallel approach scales up to approximately 2000 CPU cores. Abstract : The quantum chemical density matrix renormalization group (QC‐DMRG) method is an advanced multireference approach capable of going well beyond the limits of standard quantum chemical methods in problems where large complete active spaces are required. This article presents the new massively parallel implementation of QC‐DMRG and shows its performance on three different molecules, typical candidates for QC‐DMRG calculations. The largest calculation is the FeMoco cluster [CAS(113, 76)], which scales well up to approximately 2000 CPUs.